Importance of Labarotory Parameters in Obstructive Sleep Apnea - Ebru Ortaç Ersoy; Gülbahar Darilmaz Yüce; Serap Duru; Hikmet Firat; Sadik Ardiç; Bahar Kurt (Türk Uyku Tıbbı Dergisi, 2016)
Objective Obstructive sleep apnea (OSA) is associated with intermittent hypoxia. OSA leads to increased sympathetic activation, oxidative stress, vascular endothelial dysfunction, coagulation disorders and metabolic dysregulation. These disturbances increase the the risk of inflammation and cardiovascular diseases. The purpose of this article is to review the laboratory parameters of OSA patients without any comorbidities.